Corrosion behavior of heterogeneous grain structure FeCoCrNiMnSix (x=0, 0.1, 0.2) high-entropy alloys in sulfuric acid solution - Xianrui Zhao; Zhanjiang Li; Yulang Xu; Deyin Li; Qiangyong Zhang; Wenzhuang Lu; Pinqiang Dai (Journal of Materials Research and Technology, 2025)
FeCoCrNiMnSix (x = 0, 0.1, 0.2) high-entropy alloys (HEAs) were successfully prepared by vacuum arc melting. The alloy successfully obtained a heterogeneous grain structure after deformation and annealing. The effect of heterogeneous grain structure and Si content on corrosion resistance in sulfuric acid solution was systematically studied. The results of polarization curve and impedance spectrum curve show that with the increase of recrystal grain and Si content, the passive current density gradually decreases, and the capacitor ring gradually increases. The corrosion mechanism for all HEAs are mainly manifested as a charge transfer controlled process. The main components of the passivation film are oxides of Cr, Fe, Ni, Mn, Co and a small amount of hydroxides of Cr and Ni. The content of Mn oxide decreases with the increase of annealing temperature, and the content of Cr and Si oxide increases with the addition of Si. The improvement in corrosion resistance is mainly attributable to the reduction of high-energy and high-density dislocation regions and the increase of alloying element diffusion rate with Si addition, enhancing the stability of the passivation film.